Novel series of oligomers from 4-aminomethyl-tetrahydrofuran-2-carboxylates with 2,4-cis and 2,4-trans stereochemistry - Edwards, Alison A.; Sanjayan, Gangadharar J.; Hachisu, Shuji; Tranter, George E.; Fleet, George W. J. (Tetrahedron, 2006)
Two tetrahydrofuran-based y-amino acids [2,4-cis and 2,4-trans] were subjected to iterative peptide-coupling procedures to afford dimeric, tetrameric and hexameric carbopeptoids in good yield. These homooligomers were prepared for secondary structural study-to ascertain the conformational preference inherent in the monomer units. The L-xylo oligomers were protected with triethylsilyl ethers to increase the range of solvents suitable for structural investigation. Initial secondary structure data indicate the presence of hydrogen-bonded conformations in the L-ribo series. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Foldamers; gamma amino acids; Peptidomimetics; sugar amino acids